A economia pública municipal e o desenvolvimento regional da região Centro-Sul paranaense - Pereira, João Arami Martins (2021)
This study seeks to analyze the contribution of the public economy to the development of the Central-Southern Paraná region through the productive structure of the region's municipalities. The regional productive structure emerged with initiatives generated in agriculture, which boosted productive and business development activities during the period in which economic and institutional resources were undergoing radical changes and reformulations, leading to new alternatives for production and productive organization. Over time, the productive structure underwent changes with the creation of Industrial Districts, regional studies developed several researches with the objective of describing and interpreting these agglomerations. The State is to serve the “public interest” and thus can contribute to the effort to serve the productive structure and create possibilities for economic growth and, consequently, for regional development. Thus, the tax effort is exercised by the municipal public sector in the process of raising and allocating its own resources in the region's municipalities, with the purpose of allocating resources for their development or growth. The municipalities are structured based on transferred revenues (FPM and QPM-ICMS) and their own tax jurisdiction (IPTU, ISSQN and ITBI-IV) in the medium and long term to develop economically in the space of the Central-Southern Paraná geographic region in function of influencing the base of the productive structure, in the organization of urban and rural space, contributing to regional growth and development. Given this, this study aims to analyze the municipal public economy, through the productive structure in the geographic region of Central-South Paraná and its contribution to regional development. In this way, the productive structure is a fundamental factor for the performance of the municipal public economy and contributes to the economic growth and development of the Central-South Region of Paraná. Guarapuava still has better potential than municipalities of 20,000 to 50,000 inhabitants, which are located far from the pole city, while small municipalities have difficulties in collecting their own, with a high degree of dependence on State and Union transfers, and not track performance in relation to regional and subregional locations, hampering regional growth and development. In the central hypothesis of this thesis, it is deduced that there are several factors that can contribute to regional development, such as the implementation of a gradual performance aimed at increasing the degree of autonomy of the municipalities, which would be to diversify the productive structure, with greater public infrastructure for the implementation of industrial districts, in the provision of public services, mainly in the small municipalities that are located along the highways of the region and through technical cooperation with state and federal agencies, to expand and improve the mechanisms of taxation, collection and inspection, especially for strengthening of fiscal federalism and the regional development of the Central-South Region of Paraná.